2017
DOI: 10.1021/acs.jafc.6b05372
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hierarchical Interfacial Assembly on Lipase Stability and Performance in Deep Eutectic Solvent

Abstract: Hierarchical systems that integrate nano- and macroscale structural elements can offer enhanced enzyme stability over traditional immobilization methods. Microparticles were synthesized using interfacial assembly of lipase B from Candida antarctica with (CLMP-N) and without (CLMP) nanoparticles around a cross-linked polymeric core, to characterize the influence of the hierarchical assembly on lipase stability in extreme environments. Kinetic analysis revealed that the turnover rate (k cat) significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
(137 reference statements)
0
10
0
Order By: Relevance
“…76 Techniques and approaches for improving the biocatalytic process Immobilisation of biocatalysts, as well as the development of biphasic systems, are techniques that could lead to better process efficiency, enable easier isolation of product or biocatalyst/solvent recovery, decrease the inhibitory effect of substrate/product, and shift reaction equilibrium towards product formation (in case of a biphasic system). Examples of the immobilisation of biocatalysts when running the reactions within DES-containing systems were presented by Xu et al 69,80 Andler et al 80 demonstrated improved enzyme (lipase B from C. antarctica) performance in terms of activity and stability, together with process sustainability, in DES via hierarchical assembly (systems that integrate nano-and macroscale structural elements can offer enhanced enzyme stability over traditional immobilisation methods). Xu et al 69 studied asymmetric reduction of 3-chloropropiophenone with Acetobacter sp.…”
Section: Substrate and Co-substrate Loadingmentioning
confidence: 99%
“…76 Techniques and approaches for improving the biocatalytic process Immobilisation of biocatalysts, as well as the development of biphasic systems, are techniques that could lead to better process efficiency, enable easier isolation of product or biocatalyst/solvent recovery, decrease the inhibitory effect of substrate/product, and shift reaction equilibrium towards product formation (in case of a biphasic system). Examples of the immobilisation of biocatalysts when running the reactions within DES-containing systems were presented by Xu et al 69,80 Andler et al 80 demonstrated improved enzyme (lipase B from C. antarctica) performance in terms of activity and stability, together with process sustainability, in DES via hierarchical assembly (systems that integrate nano-and macroscale structural elements can offer enhanced enzyme stability over traditional immobilisation methods). Xu et al 69 studied asymmetric reduction of 3-chloropropiophenone with Acetobacter sp.…”
Section: Substrate and Co-substrate Loadingmentioning
confidence: 99%
“…2), may offer a unique opportunity in improving immobilized enzyme activity retention while permitting improved handling and recovery compared to traditional nanomaterials. 28,37,38
Fig. 2Fluorescein isothiocyanate tagged lactase (green) immobilized in electrospun, hierarchical nanofiber mats.
…”
Section: Enzyme Immobilizationmentioning
confidence: 99%
“…4Example of esterification reactions performed by lipase to produce value-added products from fatty acids. Reprinted with permission from Andler et al 37 Copyright 2017 American Chemical Society…”
Section: Applications Of Immobilized Enzymes In Food Waste Stream Valmentioning
confidence: 99%
“…We have previously prepared cross-linked microparticles of polydicyclopentadiene with interfacially assembled nanoparticle-conjugated lipase. Polydicyclopentadiene is a mechanically robust polymer, produced from a ring-opening metathesis polymerization. , These ∼10 μM particles showed enhanced lipase stability across a wide range of pH values and temperatures but were difficult to recover from viscous solvents . As a result, the present work synthesized lipase-containing macroscale polydicyclopentadiene HIPEs.…”
Section: Introductionmentioning
confidence: 95%